A systematic review: enhancing stroke recovery through complementary interventions—Clinical outcomes and neural activity insights - Ismail, Umi Nabilah; Yahya, Noorazrul; Wan Zaidi, Wan Asyraf; Law, Zhe Kang; Abdul Manan, Hanani (Frontiers in Neuroscience, 2024)
The growing interest in complementary interventions for stroke recovery necessitates the need for neural insights to aid in making evidence-based clinical decisions. This systematic review examined the brain activation effects of complementary therapies, including acupuncture (n = 5), motor imagery therapy (MIT) (n = 5), music (n = 3), and virtual reality (VR) interventions (n = 3), on clinical outcomes and neural activity in stroke patients. All therapies engaged motor and sensory networks, frontal regions, parietal regions, and temporal regions, suggesting their potential to improve motor control, attention, memory, and cognitive function. Acupuncture activated motor areas in both hemispheres, while MIT stimulated frontoparietal regions in both sides of the brain, supporting whole-body integration in recovery. In contrast, VR therapy exhibited ipsilesional lateralization, while music therapy showed left-lateralization. The review also found that increased interhemispheric connectivity between motor regions, along with intrahemispheric ipsilesional connectivity between motor, cognitive, and sensory areas, is key to achieving better clinical outcomes.Systematic Review Registrationhttp://www.crd.york.ac.uk/PROSPERO, identifier (ID: CRD42023455192).